Evaluation of Women’s Knowledge and Personal Preference about The Place of Delivery in Baghdad City - Sameen, entsar; Abdul Sattar, Khalida (Iraqi National Journal of Nursing Specialties, 2017)
Objective: The study aim to evaluate of women’s knowledge and personal preference about the place of delivery in Baghdad City Methodology: descriptive study conducted in baghdad city on the mothers for the period from the 14th of December, 2015 to the 14th of April 2016. The sample of study included 500 mothers who were attending to primary health care centers have been chosen sample of 26 primary health care center by a multi-stage Simple random sampling Data was collected through a constructed questionnaire, validity Data was analyzed by using of descriptive and inferential data analysis methods . Results: The results indicated that approximately (29.4%) of the mothers in the age group (20-24) and the average age of the mothers (29.97) a year and the majority of the study sample housewives and approximately (93.4%) of the level social and economic of Low & Moderate that ( 24.4%) women among the 500 chosen to the home as a place to give birth, while the majority (52.6%) chose the hospital as a place of birth for security reasons, safety, and the advice of doctors or medical The chosen of the house was for privacy reasons and social attribution.Third of the mothers do not have knowledge of pregnancy at risk and symptoms of delivery. Recommendations: Improve the maternity services at hospital to be of high quality care safe healthy & comfortable place for delivery.the obstetricians should ask all women about preferred place of delivery & try to help them according to their condition and direct them to take right choice